2016
DOI: 10.1111/dgd.12273
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phosphorylated Ser473‐Akt from translocating into the nucleus contributes to 2‐cell arrest and defective zygotic genome activation in mouse preimplantation embryogenesis

Abstract: Phosphorylated Ser473-Akt (p-Ser473-Akt) is extensively studied as a correlate for the activity of Akt, which plays an important role in mouse oogenesis and preimplantation embryogenesis. However, little progress has been made about its effect on the mouse zygotic genome activation (ZGA) of 2-cell stage in mouse preimplantation embryos. In this study, we confirmed its localization in the pronuclei of 1-cell embryos and found that p-Ser473-Akt acquired prominent nucleus localization in 2-cell embryos physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
(162 reference statements)
0
11
0
Order By: Relevance
“…Mobilization of Akt2 from the cytoplasm to the nucleus at the two-cell stage may be necessary for the occurrence of the major wave of transcriptional activation of the zygotic genome and the progression through embryo cleavages, as recently suggested by Chen et al (2016). The presence and activity of Akt2 is necessary for embryo blastomere proliferation but not other morphogenetic processes such as compaction during later cleavage stages.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Mobilization of Akt2 from the cytoplasm to the nucleus at the two-cell stage may be necessary for the occurrence of the major wave of transcriptional activation of the zygotic genome and the progression through embryo cleavages, as recently suggested by Chen et al (2016). The presence and activity of Akt2 is necessary for embryo blastomere proliferation but not other morphogenetic processes such as compaction during later cleavage stages.…”
Section: Discussionmentioning
confidence: 78%
“…It was previously shown that the pronuclear presence of p-ser-473 Akt in one-cell embryos is required for the occurrence of the first mitosis (Baran, Fabian, & Rehak, 2013). On the other hand, the nuclear localization of p-ser-473 Akt in two-cell embryos was recently associated with the major wave of transcriptional activation of the zygotic genome and the progression through embryo cleavages (Chen et al, 2016). The Akt protein described by these groups is likely to be represented by either the Akt1 or the Akt2 isoform that fertilized eggs inherit from oogenesis (Cecconi et al, 2010;Cecconi et al, 2012), which is fully active (Fiorenza et al, 2008) and likely relevant at fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…All three variants of Akt are expressed during mouse early development 50 , and the Akt pathway is present and functional in preimplantation embryos 51 . Chemical inhibition of Pi3k 52 or Akt 53 , or deletion of the master regulator genes, Pdk1 or Pten 54 , all block mouse embryo development at the 2-cell stage. Here, we observed that Akt signaling also is required for H3K36 trimethylation in 2-cell mouse embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to activate the zygotic genome is considered the main cause of 2-cell embryonic developmental arrest in mice [33,34]. It has been found that zygotic genome activation is regulated by H3K27me3, which affects the expression of zygotic genome activation genes (ZSCAN4, E1F1AX, HSPA1A, ERV4-2, and MYC), leading to the developmental arrest of 2-cell embryonic development in mice [35][36][37].…”
Section: Discussionmentioning
confidence: 99%